Retail sector’s efficiency measurement: implementation of data envelopment analysis (DEA) in hypermarket companies / Rohaida Kamaruddin and Nik Nur Ain Athirah Nik Zulkifli - Kamaruddin, Rohaida; Nik Zulkifli, Nik Nur Ain Athirah (2022)
The retail industry has been crucial to economic growth in a big way. The emergence of hypermarkets has helped contribute to the economic rapid growth. The objective of this research study is to assess the relative effectiveness of 15 hypermarket businesses in Malaysia as the Decision-Making Unit (DMU). Data Envelopment Analysis was used to measure the performance of the hypermarket companies and estimate their efficiency. Three inputs and one output were used in this project. The number of employees, stores, total assets, and total revenue were used as inputs and outputs. According to the findings of analysis, only four hypermarket companies, DMU 11, DMU 13, DMU 14 and DMU 15 with an efficiency score of 1.The rest, however, scored between 0.141541849 and 0.827074198, indicating inefficiency. DMU 15, followed by DMU 14, DMU 13, and DMU 11, served as the benchmark for 11 inefficient hypermarket among these efficient hypermarkets. In order to increase the efficiency of the inefficient hypermarket firms by employing project determination, the efficient hypermarket companies will serve as a reference set for the inefficient hypermarket companies. In order to enhance the efficiency of the hypermarket organisation, management should maximise output while maintaining a consistent level of input.